Effects of multicomponent exercise training intervention on hemodynamic and physical function in older residents of long-term care facilities: A multicenter randomized clinical controlled trial. (October 2021) - Pepera, Garyfallia; Christina, Mpea; Katerina, Krinta; Argirios, Peristeropoulos; Varsamo, Antoniou
Αbstract: Objectives: To assess hemodynamic and physical function responses during a two-month multicomponent group exercise program (MCEP) in residents of long-term care facilities. Methods: 40 older long-term care residents were randomly allocated equally to an intervention (IG; n = 20; 80 ± 7 years) and control group (CG; n = 20; 79 ± 7 years); they all submitted to hemodynamic (blood pressure and heart rate) and functional assessments before and after the MCEP. The IG performed a twice-weekly, two-months multicomponent exercise program composed of functional mobility, balance, muscle strength, and flexibility exercises; while the CG did not perform any exercise intervention. Results: There was a statistically significant decrease in systolic blood pressure (7.25 ± 14.64 mmHg; t = 2.2; effect size = 0.34; p < 0.05) following a two-month MCEP as compared with baseline. In all functional measurements (balance, mobility) were significantly improved after the MCEP (p < 0.05). Discussion: These data indicate that a two-month MCEP can improve systolic blood pressure and functionality in older residents of long-term care facilities.